FACT contrast sensitivity as a diagnostic tool in glaucoma - ŞAHİN, ÖZLEM (My University, 2008)
Purpose: To investigate spatial-contrast sensitivity (CS) assessment as a tool for diagnosis of early glaucoma in patients with good visual acuity. Methods: In this prospective cross-sectional study we evaluate done eye of 50 patients with primary open angle or normotensive glaucoma who were newly diagnosed. All met the 0.6, or better, vision requirement. CS was measured at 1.5, 3, 6, 12, and 18 cycles per degree (cpd) spatial frequencies for one luminance level (85 cd/m2) using the functional acuity contrast test (FACT). Visual fields were evaluated using the Humphrey 750i field analyzer and the 30-2 standard full threshold program. The results from the visual acuity and CS assessments were compared with results for 20 age-matched control subjects. Results: CS scores were significantly lower at all spatial frequencies for the glaucoma patients than for the control subjects. The sensitivity of CS measurements was generally around 50%. Specificity ranged between 68 and 100%. FACT CS scores of less than 22 at 12 cpd spatial frequency provided sensitivity and specificity values concomitantly exceeding 60%. Conclusions: Both the presence of a significant difference between the CS of glaucoma patients and control subjects and a high specificity of contrast sensitivity suggests that the FACT test may be used as a tool for diagnosis of patients with glaucoma, besides other methods such as short-wavelength automated perimetry (SWAP). © Springer Science+Business Media B.V. 2007.
Keywords: FACT contrast chart; Glaucoma; Sensitivity; Spatial contrast sensitivity; Specificity; Visual field